2015
DOI: 10.1001/jamaneurol.2015.0703
|View full text |Cite
|
Sign up to set email alerts
|

New Clinical Subtypes of Parkinson Disease and Their Longitudinal Progression

Abstract: IMPORTANCE There is increasing evidence that Parkinson disease (PD) is heterogeneous in its clinical presentation and prognosis. Defining subtypes of PD is needed to better understand underlying mechanisms, predict disease course, and eventually design more efficient personalized management strategies.OBJECTIVES To identify clinical subtypes of PD, compare the prognosis and progression rate between PD phenotypes, and compare the ability to predict prognosis in our subtypes and those from previously published c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
401
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 512 publications
(440 citation statements)
references
References 41 publications
34
401
2
3
Order By: Relevance
“…Patients with the same disease duration/severity may have different patterns of neuronal loss in striatal, limbic, and cortical regions 82, 83. Thus, to examine the link between disease severity and FER deficit in PD, it might be useful to employ more sensitive markers (neuroimaging) of disease progression or subtype 84. Furthermore, FER deficit could also be linked to motor asymmetries in PD, but the question of whether patients with left‐dominant motor symptoms (LPD) showing relatively greater neural degeneration in the right hemisphere have a more severe deficit than patients with right‐dominant motor symptoms remains open.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with the same disease duration/severity may have different patterns of neuronal loss in striatal, limbic, and cortical regions 82, 83. Thus, to examine the link between disease severity and FER deficit in PD, it might be useful to employ more sensitive markers (neuroimaging) of disease progression or subtype 84. Furthermore, FER deficit could also be linked to motor asymmetries in PD, but the question of whether patients with left‐dominant motor symptoms (LPD) showing relatively greater neural degeneration in the right hemisphere have a more severe deficit than patients with right‐dominant motor symptoms remains open.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…It starts with awareness of the patients' difficulties in decoding, expressing, and mimicking emotions, along with their attendant social consequences. Research on these issues could also improve medical management, as therapeutic strategies can be adapted to patients' symptoms, especially knowing that there are several PD subtypes with 3 separate phenotypes: mainly motor/slow progression, intermediate, and diffuse/malignant 84. Patients with the latter are more likely to exhibit nonmotor symptoms, including cognitive and mood disorders, but patients with the main motor form may also develop emotional impairments as a consequence of impaired facial mimicry.…”
Section: Resultsmentioning
confidence: 99%
“…This surprising finding suggests that RBD has a unique epidemiology, which is different from that of PD. There have been many studies suggesting that RBD marks a specific subtype of PD, with high risk of dementia, motor worsening, and autonomic dysfunction, termed the "diffuse-malignant" subtype [41]. If so, its environmental risk factors may also differ.…”
Section: Characteristics Of Rbd Positive Participantsmentioning
confidence: 99%
“…With long term follow-up, more than 80% of individuals with idiopathic RBD developed either Parkinson's disease (PD), dementia with Lewy bodies (DLB) or multiple system atrophy (MSA) ,Schenck, et al, 2013. It was suggested that RBD may define a subtype of PD patients (Fereshtehnejad, et al, 2015,Gagnon, et al, 2004 with cognitive decline (Gagnon, et al, 2009,Vendette, et al, 2007, dementia (Anang, et al, 2014), hallucinations (Sixel-Doring, et al, 2011) and autonomic dysfunction (Postuma, et al, 2008), as compared to PD patients without RBD. In addition, pathological studies in brains of PD patients with and without RBD demonstrated a more widespread -synuclein accumulation in those associated with RBD .…”
Section: Introductionmentioning
confidence: 99%